2009
DOI: 10.14210/bjast.v13n1.p65-70
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the constituent fatty acids of some freshwater fishes common in Nigeria

Abstract: The aim of this paper was to investigate the constituent fatty acids of some freshwater fish species as well as compare the nutritional quality of freshwater fish with that of marine fish by comparing the levels of essential fatty acids present. The fatty acids profile of freshwater fish species include minor amounts of odd-number, branched-chain, and even-number fatty acids as well as saturated components, the monounsaturated fatty acids and polyunsaturated fatty acids. The major saturated fatty acids were C1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 10 publications
5
8
0
Order By: Relevance
“…The values of PUFA/SFA (2.11–3.47) and n -6/ n -3 (0.66–1.28) ratios obtained in the present study indicated benefits in the consumption of all fish species [20]. Similar PUFA/SFA results were verified for Esox lucius (2.46) [59] and Lates niloticus (3.15) [62], whereas similar n- 6/ n- 3 values were observed for Prochilodus spp. (1.03) [8] and Cichla sp.…”
Section: Discussionsupporting
confidence: 85%
“…The values of PUFA/SFA (2.11–3.47) and n -6/ n -3 (0.66–1.28) ratios obtained in the present study indicated benefits in the consumption of all fish species [20]. Similar PUFA/SFA results were verified for Esox lucius (2.46) [59] and Lates niloticus (3.15) [62], whereas similar n- 6/ n- 3 values were observed for Prochilodus spp. (1.03) [8] and Cichla sp.…”
Section: Discussionsupporting
confidence: 85%
“…Audu, 2009;Suloma, Ogata, Garibay, Chavez, & El-Haroun, 2008) but not for their bones. There is no known metabolic role for the odd numbered fatty acids in fish and it was suggested that they might be derived from the diet with seasonal and temperature variations (Gunhild, 1989).…”
Section: Tablementioning
confidence: 99%
“…Both acids are vital for growth and development and therefore must be provided in the diet since the body cannot synthesize them. With them available, the body can [28], our determinations show that freshwater fishes can also serve as good sources of omega-3 essential fatty acids. Chief among the n-3 sources are fishes from LR, AR and TR.…”
Section: Discussionmentioning
confidence: 86%
“…Another adverse effect of high PUFA level could be the need for use of high amount of hydrogen during hydrogenation processes. Apart from the afore mentioned constraints, the present fish species (especially CG) can serve as good sources of PUFAs which are nutritionally beneficial to health, and organoleptically acceptable since they are linked with product flavor enhancement [28]. Although these fishes are good sources of EFA, at the present level of per capita fish consumption in Nigeria they are unlikely to meet the recommended daily intake of EFA (0.5 -1g/day) given in literatures [25,31].…”
Section: Discussionmentioning
confidence: 99%